Mengurangi Pengangguran Terdidik Melalui Pendidikan Kewirausahaan Yang Berpotensi Pencegahan Korupsi - Mohammad Hadi Kusuma (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Abstract: The inequality between educated job seekers and available employment causes a lot of unemployment. This is exacerbated by the number of universities that annually issue new graduates that make the number of educated unemployed. High unemployment causes the community is not able to maximize their welfare. The success of economic development can be seen from the high economic growth. Increased economic growth is expected to improve the welfare of the community and increase human development by Indicator of Index Human Development (HDI). It takes the government seriousness in addressing issues of human development improvement by reducing educated unemployment through entrepreneurial education with the potential to prevent corruption. Corruption in Indonesia requires extra thought for the government to overcome it. In accordance with the values contained in Entrepreneurship education, the government seeks to direct the Indonesian society from "finding a job" to "creating job" so that will affects in the prevention of corruption. Keywords: Educated Unemployment, Entrepreneurship Education, Corruption Prevention.